Protective effect of Mediterranean-type glucose-6-phosphate dehydrogenase deficiency against Plasmodium vivax malaria - Awab, Ghulam R; Aaram, Fahima; Jamornthanyawat, Natsuda; Suwannasin, Kanokon; Pagornrat, Watcharee; Watson, James A; Woodrow, Charles J; Dondorp, Arjen M; Day, Nicholas PJ; Imwong, Mallika; White, Nicholas J (eLife, 2021)
X-linked glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common human enzymopathy. The severe Mediterranean variant (G6PD Med) found across Europe and Asia is thought to confer protection against malaria, but its effect is unclear. We fitted a Bayesian statistical model to observed G6PD Med allele frequencies in 999 Pashtun patients presenting with acute Plasmodium vivax malaria and 1408 population controls. G6PD Med was associated with reductions in symptomatic P. vivax malaria incidence of 76% (95% credible interval [CI], 58–88) in hemizygous males and homozygous females combined and 55% (95% CI, 38–68) in heterozygous females. Unless there is very large population stratification within the Pashtun (confounding these results), the G6PD Med genotype confers a very large and gene-dose proportional protective effect against acute vivax malaria. The proportion of patients with vivax malaria at risk of haemolysis following 8-aminoquinoline radical cure is substantially overestimated by studies measuring G6PD deficiency prevalence in healthy subjects.